Nigeria : the political and economic background - The Royal Institute of International Affairs (London ; Ibadan : Oxford University Press, 1960)
This little book conveys an astonishing quantity of information in a short space without making any of the insufficiently qualified statements that beset writers obliged to compress their material. It is equally divided between political and economic topics. The first part covers the history of Nigeria up to I945 in fifteen pages, and then takes the years from the Richards Constitution at a more leisurely pace. The section on economics is readable and very informative, and there are several useful maps.
Includes bibliographical footnotes.
aia 11/04/2017
Loans
Keywords: Nigeria background; Economic conditions; Nigeria $1 (BPolitics and government $1 (BTo 1960.s; Nigeria $1 (BEconomic conditions $1 (BTo 1960.s; Nigeria